Numerical simulation of solid–liquid two-phase flow field for shellfish precooking processing machine. Issue 2 (3rd May 2020) - Zhang, Xindan; Feng, YiRan; Zhang, Xu; Lu, Jinshi; Tao, Xueheng
Abstract: In this study, a new type of shellfish precooking processing machine is designed. The corresponding three-dimensional solid model is constructed using SOLWORKS, which also introduces basic structure and working principle of shellfish precooking machine. Besides, solid-–liquid two-phase flow field for shellfish precooking processing machine is simulated by ANSYS FLUENT 15.0, which simulated the distribution of liquid flow and volume fraction of solid in the pot. The reasons of flow field distribution and the solid particle volume fraction of the liquid phase flow in the vertical and horizontal planes were analysed under different mixing speeds. According to the results, the solid–liquid two-phase flow field distribution is reasonable and turbulent region can be formed in the pot. The distribution of flow field and the texture properties of abalone were compared at three different speeds, and the more reasonable mixing speed was determined. In addition, the results of the analysis provide references for the optimisation of mixer in the future.